Scaffold hopping-guided design of some isatin based rigid analogs as fatty acid amide hydrolase inhibitors: Synthesis and evaluation - Jaiswal S.; Tripathi R.K.P.; Ayyannan S.R. (My University, 2025)
Fatty acid amide hydrolase (FAAH) represents a potential therapeutic target for number of peripheral and nervous system related disorders including neuropathic pain and neuroinflammation. A library of N-(2,4-dichlorobenzoyl) isatin Schiff bases 7a–7l and 8a–8c were designed using the contemporary scaffold-hopping approach, synthesized and investigated for their ability to inhibit human FAAH enzyme using fluorescence based Cayman assay kit. The synthesized compounds inhibited FAAH with IC50 values in the range from 1.49 to 12,858 μM. Compound, 3-(1H-benzoimidazol-2-ylimino)-1-(2,4-dichlorobenzoyl)indolin-2-one (8c) showed strong inhibition against FAAH with IC50 of 1.49 ± 0.03 μM. SAR studies revealed various structural aspects important for the potency of these analogs. In particular, our findings suggested the requirement of hydrophobic aryl/heteroaryl moiety at C-3 position of isatin for optimum rigidity and steric hindrance to the scaffold. Additionally, molecular docking studies supported the experimental results revealing that compound 8c well-occupied the enzymatic cleft with optimal binding orientation and interactions within the active site of FAAH which resulted in reduced susceptibility of compound to nucleophilic attack and prevented it from leaving the active site, thereby increasing the inhibition. Also, compound 8c presented potent antidepressant and anxiolytic properties without any neurotoxicity. In silico molecular properties and ADMET descriptors calculations related the lead FAAH inhibitor 8c presented the satisfactory drug-like characteristics and ADMET properties and thus considered for further optimization. To the best of our knowledge this is the first report on the FAAH inhibitory properties of isatin-based analogs, revealing that both indoline skeleton and heteroaryl substitution at C-3 can modulate the activity of FAAH enzyme. In conclusion, the present study provided a better understanding of the molecular fragments requisite for maintaining and/or improving FAAH inhibition activity. © 2018 Elsevier Masson SAS